Comparison of efficacy between herbal capsule of anise and mefenamic acid on postpartum after-pain - G Ozgoli; A Khodadie; Z Mojab; S Jambarsang; F Sheikhan; S Taleb (Institue of Medicinal Plants, ACECR, 2017)
Introduction: Postpartum after pain relief is effective in convenience of the mother and improve her interaction with the newborn.one of the ways of pain relief is using herbal medicines.  Aim: This study was conducted to compare the effect of mefenamic acid (the common pain reliever) and anise capsule on postpartum after-pain. Method: In this clinical trial, a randomized, double-blind study was conducted. The sample included 96 Mothers in the state of two hours after their vaginal delivery. Their intensity of the pain was between moderate and savior. Women were entered into two groups of mefenamic acid and anise capsule. The capsules were used 4 times a day (each 6 hours one capsule). The pain intensity was evaluated before intervention and one hour after each intervention by the visual analogue scale (VAS). Data was analyzed by the Statistical Package for Social Scientists (SPSS version 17). Results: The two groups were matched in the number of parity and intensity of the pain before intervention. Results revealed that the Reduction of the pain was significantly higher in the anise capsule group (p<0.05). Reduction of the pain had no relation with the number of parity(p<0.05)and both mefenamic acid and anise capsule consume the same time to effect. Conclusion:The anise capsule is effective in order to relief postpartum after-pain.